Questions of complex treatment of extensive small pelvis phlegmons in patients with diabetes mellitus - N. N. Veligotskiy; A. S. Trushin; A. I. Seroshtanov; A. A. Sheptukha; I. Ye. Bugakov; V. M. Boyev (Сучасні медичні технології)
The complex treatment results of 127 patients with extensive purulent processes in diabetes mellitus that were treated in our clinic with ozone therapy and ultrasonic cavitations at 2001–2018 are presents. The problems of the course of the disease and the aggravating influence of the accompanying pathology on it are noted. The options improving the results of treatment considered.